Reconceptualising language immersion pedagogy for rural education through teachers’ online learning community - Lorrendah Joseph; Rosy Talin; Cynthia C. James; Sara Hennessy; Kean Wah Lee (Faculty of Education and Sports Studies Universiti Malaysia Sabah, 2024)
The language immersion pedagogy posits that the more time devoted to studying a second/foreign language, the higher the proficiency attained. The nationwide Highly Immersive Programme (HIP) in Malaysia incorporates the guiding principles of the language immersion framework in its effort to enhance students’ English language proficiency. Schools operating under the auspices of the Ministry of Education are mandated to establish a language environment that is immersive, fostering language usage through a diverse range of extracurricular and classroom-based activities. Although several studies have examined HIP’s efficacy and the challenges associated with its execution in different settings, there is a lack of discourse regarding the programme’s theoretical foundations and its connection to practical applications. Particularly, there is a lacuna of empirical investigations on the programmes’s feasibility in rural and low-resource contexts. This paper aims to report preliminary findings from a pilot study in two rural primary schools in Sabah, Malaysia. Adopting a design-based research methodology within an online learning community, this study aims to redefine the concept of “immersive language environment.” For 16 weeks, participating teachers have undertaken school-based inquiries, collaborative lesson planning, and materials development. Data are derived from video recording of pupils’ learning activities, transcripts of teachers’ online discussions, digital artefacts, and interviews. Findings are presented through a case study method. Implication from the findings leads towards deeper investigation of teachers’ collaborative learning, Utilising learners’ native languages and cultural repertoires as resources for language immersion pedagogy seems to enhance teachers’ understanding of inclusivity, culturally responsive pedagogy, and interculturality.